Efektivitas Penyidikan Tindak Pidana Pemalsuan Dokumen Regident Buku Pemilik Kendaraan - Burhan, Burhan; Rahman, Sufirman; Razak, Askari (Program Pascarajana Universitas Muslim Indonesia, 2023)
Tujuan penelitian menganalisis dan mengevaluasi efektivitas penyidikan tindak pidana pemalsuan dokumen regident buku pemilik kendaraan di Polda Sulawesi Selatan dan faktor-faktor yang mempengaruhi efektivitas penyidikan tindak pidana pemalsuan dokumen regident buku pemilik kendaraan di Polda Sulawesi Selatan. Penelitian ini adalah penelitian empiris. Hasil penelitian ini menunjukkan: 1) efektivitas penyidikan tindak pidana pemalsuan dokumen regident buku pemilik kendaraan di Polda Sulawesi Selatan kurang efektif, 2) Faktor-faktor yang memengaruhi efektivitas penyidikan tindak pidana pemalsuan dokumen regident buku pemilik kendaraan di Polda Sulawesi Selatan adalah faktor substansi hukum, faktor struktur hukum, faktor budaya hukum dan faktor sarana dan prasarana. The research objective is to analyze and evaluate the effectiveness of the investigation into the criminal act of falsifying vehicle owner registration documents at the South Sulawesi Regional Police and the factors that influence the effectiveness of the investigation into the criminal act of falsifying vehicle owner registration documents at the South Sulawesi Regional Police. This research is empirical. The results of this research show: 1) the effectiveness of the investigation into the criminal act of falsifying vehicle owner registration documents at the South Sulawesi Regional Police is less effective, 2) The factors that influence the effectiveness of the investigation into the criminal act of falsifying vehicle owner registration documents at the South Sulawesi Regional Police are the legal substance factor, legal structure factors, legal culture factors and facilities and infrastructure factors.